The First Reported Pediatric Case of Primary Myoepithelial Carcinoma Involving the Whole Lung: Surgical Radical Treatment and Prosthesis Implant - Claudia Filisetti; Tiziana Russo; Andrea Pansini; Claudio Vella; Camilla Viglio; Giovanna Riccipetitoni (Georg Thieme Verlag KG, 2020)
Primary myoepithelial carcinoma of the lung (PMC-L) arising from the bronchial glands in lower respiratory tract is exceedingly rare. Thus far, few cases in adults and only one in a pediatric patient have been recorded. To our knowledge, this is the first report of PMC-L successfully removed in a child, focusing on the importance of multidisciplinary primary surgery for the treatment of this tumor. A 7-year-old girl was admitted for persistent cough and fever; she was unresponsive to oral antibiotics. Chest radiography showed loss of volume of left lung sustained by almost total atelectasis. After routine clinical investigations, she was referred for computed tomography scan and magnetic resonance imaging that documented the presence of a mass occupying the entire left upper lobe, infiltrating the pulmonary hilum (main bronchus, pulmonary artery, superior pulmonary vein, and pericardium). After multidisciplinary evaluation, the histopathologic diagnosis of PMC-L was established using ultrasonography-guided transthoracic core needle biopsy and bronchoscopic biopsies. She was then subjected to left pneumonectomy under extracorporeal circulation and positioning of a thoracic expander filled with 200 mL of saline solution. The postoperative course was uneventful. With TREP (very Rare Tumor in Pediatric Age) consent radiotherapy was performed (61.2 Gy). At the 10-month follow-up, the patient was alive, breathing normally without any oxygen support, without recurrence of PMC-L or metastasis, and without any chest deformity. To our knowledge, this is the first case where a pediatric patient was successfully operated for PMC-L involving the whole lung. Extracorporeal circulation enabled us to perform radical primary surgery. Prosthesis implant not only maintained normal chest expansion but also allowed focused radiotherapy, thus enabling us to prevent damage to vital organs.